The Reliability Analysis for Force Concept Inventory - Binti Murshed, Mazlena; Aliah Phang, Fatin; Abd Hadi Bin Bunyamin, Muhammad; Jalilah Binti, Ibnatul (International Journal of Psychosocial Rehabilitation, 2020)
Force Concept Inventory (FCI) is a diagnostic test that is commonly used to measure the concept of knowledge based on force and motion. This study examines the validity and reliability of FCI using a new item analysis method. The Rasch Measurement Model (RMM) enables the construction of linear scales for individuals (persons) and items from raw test scores. This model can provide valuable insights into the structure and function of the test regarding the difficulty distribution of the test item. It can also predict to what extent it fits the model, and the items can also determine its basic structure. The data for Rasch’s analysis were obtained from a pilot study involving 78 high school students (16 to 17 years old) who took a physics subject. The reliability of FCI items is high, and it is proven that it can measure conceptual understanding. Thus, this test can determine the level of conceptual understanding of force and motion.